Effect of Potassium Chloride and Sodium Bicarbonate in drinking water on heat stressed Broiler performance and blood profile (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to investigate the effect of adding Potassium Chloride and Sodium Bicarbonate in drinking water on growth performance and blood haematological and biochemical parameters of broiler chicks reared during summer (April-May).experiment consisted of four treatments (T): treatment A (ontrol)water with no salt supplement, treatment B water was supplemented with 0.7% Potassium Chloride, (T) C 0.7% Sodium bicarbonate was added,(T)D combination of 0.7% KCl and 0.7% NaHCO3was added. A total of 96 one-day unsexed broiler chicks (ROSS) were used. Birds were allocated into 4×3×8 completely randomized design. Feed intake, live body weight, weight gain and Feed conversion ratio (FCR) were measured. Blood haematological parameters (packed cell volume PCV, Red blood cells and white blood cells) and biochemical parameters (total protein, phosphorus, potassium and sodium) were measured. The results showed numerical increase (p0>.05) in weight gain and live body weight and carcass weight when a combination of KCl and NaHco3 was supplemented in drinking water. Feed intake and feed conversion ratio were not affected (p>0.05) by the different treatments. Water consumption was increased (p< 0.05) when electrolytes were added. There was no significant effect (P>0.05) observed in (Total white blood cells, heterophils, Neutrophil, Basophill). However, Lymphocyte decreased significantly (p